2022
DOI: 10.1039/d2nr02278h
|View full text |Cite
|
Sign up to set email alerts
|

Green chemistry and first-principles theory enhance catalysis: synthesis and 6-fold catalytic activity increase of sub-5 nm Pd and Pt@Pd nanocubes

Abstract: Synthesizing metal nanoparticles with fine control of size, shape and surface properties is of high interest for applications such as catalysis, nanoplasmonics, and fuel cells. In this contribution, we demonstrate...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…322−324 In addition to facet-selective diffusion and deposition induced by capping agents, a joint experimental-theoretical study showed that facet-selective reduction kinetics could underlie the solution-phase growth of Pd nanocubes and penta-twinned nanowires induced by bromide and formic acid in solution. 311 Mastronardi et al used DFT-based ab initio thermodynamics to show there is a synergy between the adsorption of Br and COOH, a decomposition product of formic acid on Pd (111) and Pd (100). The calculations predicted that {100} facets contained a mixture of Br and COOH, or just COOH, while {111} facets contained no COOH at high Br and formic acid concentrations, consistent with experimental conditions under which Pd cubes and pentatwinned nanowires formed.…”
Section: Kinetic Wulff Shapesmentioning
confidence: 79%
See 2 more Smart Citations
“…322−324 In addition to facet-selective diffusion and deposition induced by capping agents, a joint experimental-theoretical study showed that facet-selective reduction kinetics could underlie the solution-phase growth of Pd nanocubes and penta-twinned nanowires induced by bromide and formic acid in solution. 311 Mastronardi et al used DFT-based ab initio thermodynamics to show there is a synergy between the adsorption of Br and COOH, a decomposition product of formic acid on Pd (111) and Pd (100). The calculations predicted that {100} facets contained a mixture of Br and COOH, or just COOH, while {111} facets contained no COOH at high Br and formic acid concentrations, consistent with experimental conditions under which Pd cubes and pentatwinned nanowires formed.…”
Section: Kinetic Wulff Shapesmentioning
confidence: 79%
“…For larger nanocrystals, surface diffusion on the facets can occur on the time scale of deposition. Studies have considered this scenario. …”
Section: Kinetics Of Nanocrystal Structurementioning
confidence: 99%
See 1 more Smart Citation
“…26,28,[33][34][35][36] Furthermore, it has been demonstrated that PtNP size and shape can signicantly modulate their catalytic properties, opening the possibility of tailored design and/or maximization of the catalytic activity of the nanoparticles. [37][38][39][40] In this application, we designed a hybrid system combining 5 nm Pt nanozymes with a paper-based device engineered with a multi-line Pt-based Lateral Flow Assay (LFA). Notably, this innovative strategy allows a semi-quantitative evaluation of TAC, providing a direct colorimetric readout within 10 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology and biotechnology also satisfactorily contribute to green chemistry through the synthesis of metallic nanoparticles for catalysis, nanoplasmonics, and fuel cells [34]. Research on blue-green-emitting fluorescent copper nanoclusters seeks easier analytical methods for myoglobin and L-thyroxine quantification.…”
Section: Introductionmentioning
confidence: 99%